Improving the Irrigation Systems for the Fallujah Irrigation Projects by Using Water Evaluation and Planning Model (WEAP) - Hamdi, Aya; Abdulhameed, Isam; Mawlood, Ibtihal (Anbar Journal of Engineering Sciences, 2023)
In this study, the water evaluation and planning WEAP model was used to improve the Fallujah irrigation project with 63,000 hectares and an annual budget get 1,476 million m3/ yiod (2020-2021). The results showed the total Water used was 1,272 million m3/year and equaled 86% of Fallujah irrigation budget. The annual production was 524.4 million Kg/year for Fallujah irrigation, and total economic returns were 393.6 million $/year. The study outlined two scenarios for enhancing the irrigation system. The first scenario entailed implementing a sprinkler irrigation system for wheat and barley across all projects. This resulted in a production increase from 524.4 to 625.7 million kilograms per year and a corresponding rise in economic returns from 393.6 to 427.2 million annually. In the second scenario, a sprinkler system was adopted for wheat and barley and a trickle system for other crops. This approach led to production growth from 524.4 to 1164.9 million kilograms per year and a surge in economic returns from 393.6 to 559.4 million annually.